Safety and efficacy of paramedic treatment of regular supraventricular tachycardia: a randomised controlled trial. Issue 18 (9th September 2016) - Honarbakhsh, S; Baker, V; Kirkby, C; Patel, K; Robinson, G; Antoniou, S; Richmond, L; Ullah, W; Hunter, R J; Finlay, M; Earley, M J; Whitbread, M; et al.
Abstract : Introduction: Supraventricular tachycardias (SVTs) are a common cause of acute hospital presentations. Adenosine is an effective treatment. To date, no studies have directly compared paramedic-with hospital-delivered treatment of acute SVT with adenosine. Method: Randomised controlled trial comparing the treatment of SVT and discharge by paramedics with conventional emergency department (ED)-based care. Patients were excluded if they had structural heart disease or contraindication to adenosine. Discharge time, follow-up management, costs and patient satisfaction were compared. Results: Eighty-six patients were enrolled: 44 were randomised to paramedic-delivered adenosine (PARA) and 42 to conventional care (ED). Of the 37 patients in the PARA group given adenosine, the tachycardia was successfully terminated in 81%. There was a 98% correlation between the paramedics' ECG diagnosis and that of two electrophysiologists. No patients had any documented adverse events in either group. The discharge time was lower in the PARA group than in the ED group (125 min (range 55–9513) vs 222 min (range 72–26 153); p=0.01), and this treatment strategy was more cost-effective (£282 vs £423; p=0.01). The majority of patients preferred this management approach. Being treated and discharged by paramedics did not result in the patients being less likely to receive ongoing management of their arrhythmia and cardiology follow-up. Conclusions: Patients with SVT can effectively and safely be treated with adenosine delivered by trained paramedics. Implementation of paramedic-delivered acute SVT care has the potential to reduce healthcare costs without compromising patient care. Trial registration number: NCT02216240.